Compact wideband antenna array with DGS-based metamaterial for efficient smartphone communication and SAR reduction - Al Gburi, Ahmed Jamal Abdullah; Megahed, Amany A.; Hussein Abdullah, Amr Hussein; Elabd, Rania Hamdy (Electromagnetics Academy, 2025)
This study investigates a high-gain, miniaturized antenna array featuring semicircular Defected Ground Structures (DGSs) based metamaterial designed for wideband smartphone applications. The antenna array, measuring 49 × 25 mm2, is constructed on an FR4 substrate with a dielectric constant of 4.3 and a thickness of 1.6 mm. The design incorporates two orthogonal antennas, each with a U-shaped radiating patch and a semicircular DGS to control bandwidth and reduce size. A T-shaped stub is positioned at the center of the U-shaped radiating area, with a star-shaped element attached to the leg of the T-shaped stub to enable wideband operation. The antenna demonstrates strong S11 performance, achieving approximately −38 dB at 5.8 GHz and −42 dB at 8.1 GHz, making it ideal for Sub-6 GHz and C-band applications. The proposed antenna array operates across a frequency range from 4 GHz to beyond 10 GHz, reaching a peak gain of 11 dBi and an efficiency of 95%. A time-domain analysis was conducted to verify radiation efficiency, and the specific absorption rate (SAR) is approximately 0.0475 for 1 g of tissue and 0.0101 for 10 g of tissue at 4.5 GHz, confirming the array’s suitability for wideband smartphone devices within the target frequency band. The simulated and experimental results of the proposed antenna array show excellent agreement.